Documenting the challenges of conducting research on sexual and reproductive health and rights (SRHR) of persons with disabilities in a low-and-middle income country setting: lessons from Bangladesh. Issue 12 (17th December 2020) - Amin, Amina; Das, Adity Shayontony; Kaiser, Adrita; Azmi, Raia; Rashid, Sabina Faiz; Hasan, Md Tanvir
Abstract : Research has shown that persons with disabilities require greater sexual and reproductive health (SRH) care and services than persons without disabilities. However, this need is often neglected in most of the low-and-middle-income countries including Bangladesh. There is also a dearth of research and data relevant to this issue. A nationwide mixed-methods research has been conducted to explore persons with disabilities' specific sexual and reproductive health and rights (SRHR) needs, health seeking behaviour related to SRH and barriers in accessing SRH services, along with the associated factors that influence their SRH outcomes. The purpose of this paper is to discuss the challenges encountered by the researchers while conducting this research and the strategies adopted to resolve those challenges. Some of the challenges experienced by the researchers include development of appropriate tools with questions on sensitive SRHR topics, obtaining informed consent, difficulty to maintain privacy while exploring sensitive SRHR issues and communication difficulties when interviewing individuals with intellectual and sensory impairments. The mitigation strategies include iterative revisions of all tools based on multiple pretests in different filed sites and expert feedback, strategic rapport building and maintaining appropriate contextual etiquette while conducting the interviews. The reflections discussed in this paper will assist future researchers in understanding potential field challenges they might encounter in similar low resource settings while conducting research on SRHR and similar sensitive issues among marginalised population groups, such as persons with disabilities.